2016
DOI: 10.4168/aair.2016.8.6.512
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Visits for Asthma Exacerbation due to Weather Conditions and Air Pollution in Chuncheon, Korea: A Case-Crossover Analysis

Abstract: PurposeThis retrospective study was conducted to estimate the effects of climate factors and air pollution on asthma exacerbations using a case-crossover analysis.MethodsPatients who visited the emergency department (ED) of 2 university hospitals in Chuncheon for asthma exacerbations from January 1, 2006, to December 31, 2011, were enrolled. Daily average data for meteorological factors (temperature, daily temperature range, relative humidity, wind speed, atmospheric pressure, presence of rain, solar irradiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 31 publications
0
12
1
4
Order By: Relevance
“…Some researchers notice a significant increase in asthma exacerbation cases under the weather conditions characterized by higher ambient air humidity, and link this fact to higher counts of fungal spores [61][62][63] . Kwon et al associated this phenomenon with the occurrence of fog, which often accompanies higher air humidity, and which alone -by being acid aerosol -is yet another air pollutant 64 . Others emphasize an increase in hospital admissions due to asthma on days with lower air humidity 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers notice a significant increase in asthma exacerbation cases under the weather conditions characterized by higher ambient air humidity, and link this fact to higher counts of fungal spores [61][62][63] . Kwon et al associated this phenomenon with the occurrence of fog, which often accompanies higher air humidity, and which alone -by being acid aerosol -is yet another air pollutant 64 . Others emphasize an increase in hospital admissions due to asthma on days with lower air humidity 65 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, we could not analyze the potential variables that affect the frequency of visits and prognosis due to the retrospective nature of this study. For instance, adherence to medication, the dose of the inhaler, socio-economic status, clinical characteristics, residential district, and weather may be influential factors [ 26 , 27 ]. In this retrospective study, which used claim data from a national medical insurance review system, the available variables were extremely restricted.…”
Section: Discussionmentioning
confidence: 99%
“…It is uncertain whether the effect of humidity on AEs is direct or indirect (because humidity is related to aeroallergen and air pollutant levels). 24 Several studies showed that AE events were directly associated with high humidity, 11,13,25 but another study showed that AE events were associated with low humidity. 26 Our results showed that humidity had a significant effect on AEs in the single model but not in the final model.…”
Section: Weather Conditionsmentioning
confidence: 99%